2009
DOI: 10.1111/j.1600-6143.2009.02815.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Gastric Submucosal Transplantation of Islets (ENDO-STI): Technique and Initial Results in Diabetic Pigs

Abstract: The results of transplantation of human donor islets into the portal vein (PV) in patients with diabetes are encouraging. However, there are complications, for example, hemorrhage, thrombosis and an immediate loss of islets through the 'instant blood-mediated inflammatory reaction' (IBMIR). The gastric submucosal space (GSMS) offers potential advantages. Islets were isolated from adult pigs. Recipient pigs were made diabetic by streptozotocin. Donor islets were injected into the GSMS through a laparotomy (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 30 publications
(34 reference statements)
0
63
3
4
Order By: Relevance
“…In a mouse model, syngeneic rodent islets transplanted into the femur are able to reverse hyperglycemia without any evidence of derangement of the hematopoietic system or disruption of structural integrity (Cantarelli et al 2009). Another promising site is the gastric submucosal space (GSMS) (Echeverri et al 2009;Wszola et al 2009). After endoscopic placement, islets would benefit from a rich blood supply and a high oxygen tension.…”
Section: Alternative Transplant Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model, syngeneic rodent islets transplanted into the femur are able to reverse hyperglycemia without any evidence of derangement of the hematopoietic system or disruption of structural integrity (Cantarelli et al 2009). Another promising site is the gastric submucosal space (GSMS) (Echeverri et al 2009;Wszola et al 2009). After endoscopic placement, islets would benefit from a rich blood supply and a high oxygen tension.…”
Section: Alternative Transplant Sitesmentioning
confidence: 99%
“…After endoscopic placement, islets would benefit from a rich blood supply and a high oxygen tension. Preclinical trials using a porcine model showed reduced early islet loss and insulin requirements when GSMS islets were compared to intraportal islets (Echeverri et al 2009). …”
Section: Alternative Transplant Sitesmentioning
confidence: 99%
“…The feasibility of MR imaging of transplanted islets in a clinical situation was assessed by in vivo imaging of islet engraftment in a swine model. Because swine islets are rapidly destroyed during transplantation (22), the recipient swine was treated with immunosuppressive drugs (23). The transplantation was then performed by an interventional radiologist (24).…”
Section: In Vivo Mr Imaging Of Immune Rejection Of Transplanted Allogmentioning
confidence: 99%
“…This study showed that the striated muscle could be a promising site for islet transplantation that promotes full revascularization of Curr Radiol Rep (2013) 1:205-215 209 implanted grafts. Besides the forearm muscle, several other islet transplantation sites including the gastric submucosal space [80,81] and adrenal glands [82] have also been investigated. Clearly, non-invasive imaging could greatly assist in evaluating these sites and in monitoring islet survival aiding to clinical translation of these new approaches.…”
Section: Mri Tracking Of Transplanted Isletsmentioning
confidence: 99%